2015
DOI: 10.1007/s00383-015-3742-8
|View full text |Cite
|
Sign up to set email alerts
|

Rectal suction biopsy for the diagnosis of Hirschsprung’s disease: a systematic review of diagnostic accuracy and complications

Abstract: RSB combined with AChE staining is a simple, safe and accurate method for the diagnosis of HD. The risk for RSB-related complications is higher in newborns and infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
79
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 61 publications
3
79
1
1
Order By: Relevance
“…Some authors have suggested performing RSB only in newborn infants with neonatal onset of symptoms [35,36], whereas others also advocate this in patients that present later in life [37,38]. A recent systematic review has indicated that the likelihood of RSB-related complications appears to be higher in newborns and young infants compared to older children [12]. In contrast, Keyzer-Dekker et al [39] found that RSB can also be reliably and safely performed in preterm infants, which implies that there is no reason to postpone a RSB in these patients.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Some authors have suggested performing RSB only in newborn infants with neonatal onset of symptoms [35,36], whereas others also advocate this in patients that present later in life [37,38]. A recent systematic review has indicated that the likelihood of RSB-related complications appears to be higher in newborns and young infants compared to older children [12]. In contrast, Keyzer-Dekker et al [39] found that RSB can also be reliably and safely performed in preterm infants, which implies that there is no reason to postpone a RSB in these patients.…”
Section: Discussionmentioning
confidence: 95%
“…In 2006, Dutch researchers compared the accuracy of different tests for diagnosing HD and showed that RSB stained for acetylcholinesterase is the most accurate test for patients with suspected HD [30]. More recently, another systematic review has revealed that RSB provides in almost 90 % adequate tissue samples for the diagnosis of HD, with mean sensitivity and specificity rates of approximately 97 and 99 %, respectively [12]. On the other hand, it has been reported that RSB identifies HD in patients \39 days of age with a sensitivity of only 50 %, thus frequently leading to inconclusive results with need for additional biopsies [31].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[9] A recent systematic review demonstrated an average sensitivity and specificity of SRB of 96.8% and 99.4%, respectively, when compared against full thickness biopsy. [10] Very few studies detailing the accuracy of SRB in preterm infants exist at present. Collectively, these studies noted a high degree of sensitivity and specificity of SRB for HD, but many of the patients underwent their biopsies close or after 40 week gestational age.…”
Section: Discussionmentioning
confidence: 99%